Introducing a Novel Method: Validating Overspending Measurements in Hungary - Tiḿea Vastag; Boglaŕka Eisinger-Balassa (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
Preliminary research showed how the existing publications approach households' spending habits from a quantitative point of view. Questionnaires and their statistical evaluation by the appropriating software are the most commonly used in the reviewed studies. Analysing a family's overspending in Hungary was planned based on the available statistical data in the Hungarian Statistical Office (KSH). Checking the databases showed discrepancies; therefore, the inquiry of existing secondary data provides an alternate solution for describing the Hungarian situation. Two qualitative data analysis software were used to validate the two-level analysis. On the macro level, Research Rabbit provided data for structuring the sources on a timeline. On the micro level, an in-text analysis was carried out with the help of NVivo 14 Software based on the references from the Web of Science database. At the end of the paper, the conclusion was that a transdisciplinary approach is required to cover the reasons for families' overspending holistically. Calculating a Reference Budget will be a method that can be validated in Hungary to provide theoretical and practical implications.
Keywords: M00; 330; household; spending habit; statistics; new method; nVivo; text mining